Pengaruh Model Numberred Heads Together (NHT) Berbantuan Media Kantong Matika Terhadap Hasil Belajar Matematika: This study aims to determine whether the Numberred Heads Together (NHT) model with the help of bag matics media has an effect on the mathematics learning outcomes of fourth grade students in Pingit Village, Pringsurat District, Temanggung Regency. This research is a type of Quasi-Experimental research with a Non Equivalent Control Group Design model. The sample used was 20 students in class IV consisting of 10 students as the control class and 10 students as the experimental class. The sampling technique used is saturated sampling. Method of collecting data using tests that have been tested for validity using the product moment technique and reliability testing using the Cronbach alpha formula. Data analysis used non-parametric statistical techniques Mann Whitney U test assisted by the IBM SPSS Statistic 24 program with a significance level 5%. This is evidenced by the difference in the average post-test result of the control class and the experimental class. The control class average was 57,7 and the experimental class average was 85 after being given treatment. Results of hypothesis testing carried out using the Mann Whitney U test assisted by the IBM SPSS Statistic 24 program, the Z value obtained is -3,797 with Asymp. Sig. (2-tailed) of 0,001 < 0,05. Based on this research, it can be concluded that the use of the Numberred Heads Together (NHT) model with the help of bag matics media has an effect on learning outcomes in mathematics. - Listiawati, Anis; Japar, Muhammad; Pradana, Agrissto Bintang Aji (Prosiding University Research Colloquium, 2021)
This study aims to determine the effect of of Teams Games Tournament (TGT) learning model with monopoly game media on mathematical logic intelligence in grade V Student of SD Negeri Keji 2, Muntilan District, Muntilan Regency. This type of research is pre-experimental with one group pretest-posttest design. The sample taken in class V SD Negeri Keji 2 with a total of 18 students. The sampling technique used was saturated sampling. Test data analysis using prerequisite test or normality test and hypothesis testing. Data retrieval through multiple choice test questions was then analyzed using the Wilcoxon test in the SPSS 23.00 program for windows. The results showed that the Teams Games Tournamnet learning model with monopoly game media had an effect on students mathematical logis intelligence. This is evidenced by the results of the analysis of the Wilcoxon signed rank test analysis of-3.732 with Asymp. Sig 2 tailed is 0,000 < 0,005. So that Z output < mean rank or 3,732 < 9,50 Ha is accepted and Ho is rejected. The data identify the data points are smaller than the average. Based on the result of the analysis the and discussion, there are differences in the in the results of the average value, namely the initial measurement (pretest) of 41,3 and the final measurement (posttest) of 73,1. From the results of the study it can be concluded that the Teams Games Tournament (TGT) learning model with monopoly game media has an effect on students mathematical logic intelligence.